Investigating Enterprise Risk Management Policy in Selected UAE Higher Education Institutions - IBRAHIM, YASER ABDULRAHMAN (2022)
Despite its challenging nature, recent educational research has proven that the implementation of enterprise risk management (ERM) in higher education can be successful and effective in many countries around the world. Since the introduction of a risk-based assessment and accreditation system by United Arab Emirates (UAE) higher education licensure and accreditation authorities in 2001 (updated in 2011 and 2019), there have been few academic studies and little research to investigate the effectiveness of ERM implementation in UAE higher education institutions (HEIs). Moreover, even fewer studies have shed light on the major constructs of quality assurance and academic effectiveness in the context of ERM and risk management from the UAE higher education perspective. This research investigates the effectiveness of ERM implementation in HEIs, with specific focus on selected UAE HEIs. The purpose of this study is twofold: to investigate the perceptions surrounding the effectiveness of ERM (as an academic accreditation, assessment and evaluation tool) and its implementation in UAE HEIs, and to propose a set of workable guidelines for UAE HEIs in relation to effective ERM implementation strategies. The Theoretical Framework of this study is built on three major institutional theories: Institutional Organisational Theory, Legitimacy Theory and Organisational Change Theory. These theories were chosen by the researcher based on the premise that they would lead to improved understanding of the research findings by informing the conceptual analysis and deciding the type of literature to rely on. The justification for the choice of each such theory was based on the nature of each of the research questions, as well as the expected outcomes. In this sense, the findings related to the relationship between the factors leading to HEI adoption and the implementation of ERM would be best represented in the concepts of Institutional Organisational Theory, while those findings that touch upon the effectiveness of the ongoing academic processes involved in ERM implementation correspond to the Organisational Change Theory. In terms of methodology, the researcher investigated and examined the major constructs of the study through a sequential mixed-method study design, utilising both quantitative and qualitative research instruments. The participants of the quantitative study were conveniently selected, while the interviews participants for the qualitative study were purposively selected from major HEIs in the UAE. The researcher mainly used a quantitative research tool through a survey questionnaire to obtain data based on the participants’ perceptions, and to examine ERM maturity levels across the selected HEIs. The participants of the survey, as well as the interviews, were selected faculty members and academic administrators whose views, professional experience and academic knowledge are indispensable for the process of academic evaluation and assessment and ensuring quality assurance. The qualitative study was carried out through two phases: first by conducting document analysis, where the themes and data obtained from the document analysis informed the researcher on the current status of risk management and ERM policies’ and manuals’ applicability and integration into the targeted HEIs’ academic processes; while the second phase of the qualitative study consisted of semi-structured interviews conducted with five purposively selected faculty members and administrators with major risk management, quality assurance and academic effectiveness responsibilities. The findings of the quantitative survey answered the major research question regarding the identification of the participants’ perceptions of ERM implementation in UAE HEIs and showed that the majority of the participants agreed with the major premise of the study, namely that the effective implementation of ERM leads to proven and sustainable academic effectiveness. The themes elicited from both document analysis and semi-structured interviews highlighted the major characteristics of applied risk management policies and gave hints of what ERM implementation strategies need to be adopted in UAE HEIs in order to best achieve academic effectiveness and meet quality assurance requirements. This study concludes by proposing guidelines and recommendations for optimum ERM implementation strategies that may be adopted in higher education contexts in order to achieve more effective and enhanced ERM integration across all institutional processes. By doing so, this research helps identify the current theoretical and practical features of ERM implementation in UAE HEIs and suggests better strategies for the more effective implementation of ERM. It also paves the way for further study that may consider among other factors the quality and effectiveness of academic programmes and processes in UAE HEIs in terms of ERM adoption and implementation. Therefore, the study resulted in major contributions to literature, theory, methodology and finally policy and practice. In terms of contribution to literature and theory, it helped establish a link between ERM research done internationally and research that can be conducted in UAE higher education context. It has also contributed to the establishment of a theoretical framework that can be used to inform future research in similar areas and in similar contexts. In this way, the study highlights the view that the academia is a unique entity that has a unique purpose and perspective to ERM, different from other organisations’ purpose and perspectives of ERM. Contributions to policy and practice are represented by proposing a set of guidelines that aim at refining the ERM implementation strategies in higher education institutions, particularly in the UAE context.